TRAINING OF COMMUNICATION BASIC SKILL TO DEVELOP PROFESSIONAL COMPETENCE OF COUNSELING AND GUIDANCE TEACHERS - Bahar Karim Usman; Roslina Math (Scolae: Journal of Pedagogy, 2020)
This study aims to elaborate the forms and results of the application of basic communication skill training in developingthe professional competence of guidance and counseling teachers. The subject of the current research is a guidance andcounseling teacher who is on duty at SMK Dirgantara, Makassar City. The research method is quantitative descriptive,namely numerical data obtained by using a questionnaire is used as the determinant factor in achieving the results of theresearch. The data is then described based on theoretical studies to support the finding data. The type of this research isex post facto with a simple regression formula. From the result of the research and the analysis, three basic types ofcommunication skills that are applied by counseling guidance teachers in developing professional competence arefound, namely identification of the communication process, skills of receiving and conveying information, and choosingthe right communication media. Furthermore, it is concluded that training of basic communication skills does not have asignificant effect on the development of teacher professional competence at SMK Dirgantara Makassar. This isindicated by the regression line formed namely the mathematical relationship between the independent variable(training of basic communication) with the dependent variable (the development of the teacher professionalcompetence).